Implementation of WHO Surgical Safety Checklist and its Outcome in South Asia - Kurlberg, Göran (Journal of Institute of Medicine Nepal, 2019)
Introduction Surgery plays an essential role in any health care system. In 2009, WHO introduced the safe surgery checklist, to improve patient outcome following surgical procedures. The purpose of this trial was to elucidate the effects of the checklist on perioperative complications and checklist implementation at different hospitals in South Asia. Methods Online databases were searched to find relevant publications at centres in the South Asian Association for Regional Cooperation (SAARC) area. They were characterised regarding type of study, publication details, study population as well as type of intervention, by the use of the WHO checklist. Results Following the search process, seven full text publications were included in the review. They emanated from five medical centres in India and two from Pakistan. All of these reports found a clear improvement in surgical outcomes and the implementation approached 90-96%. Conclusion The WHO checklist is a valuable tool to reduce surgical complications, especially in resource-limited settings, where it should be more commonly used.